An altered Bioheat model for persons with cervical spinal cord injury. (October 2018) - Mneimneh, Farah; Ghaddar, Nesreen; Ghali, Kamel; Omeis, Ibrahim; Moussalem, Charbel
Abstract: The objective of this work is to develop a Bioheat model to predict the thermal responses of people with tetraplegia (TP) under hot, cold and neutral ambient conditions as well as different physical activities suitable for their level of injury. The focus is on TP with impairment or loss of motor and/or sensory function in C1 to C7 segments of the spinal cord due to damage of neural elements within the spinal canal. Starting from transient multi-segmented Bioheat model of able-bodied (AB) people, specific modifications were performed reflecting the changes in physiology due to the injury affecting the blood circulation system, energy expenditure, and thermoregulatory functions in the body. The TP Bioheat model predicts the TP thermal responses under steady and transient thermal conditions, and different activity levels that are appropriate for the level of injury. The model was validated with published experimental data reporting physiological and thermal data measurements on cases of people with complete and incomplete tetraplegia under controlled environmental conditions and activity levels. In both transient and steady state environmental conditions, the predicted core and mean skin temperature values were compared against the experimental data with maximum error of 0.86 °C and 0.9 °C respectively. The TP Bioheat model can be used as a tool to propose appropriate personal cooling strategies for TP. Graphical abstract: Highlights: Thermophysiology of people with tetraplegia (TP) is changed after spinal cord injury. A robust bioheat model is needed to predict thermoregulatory responses in TP. A complicated detailed bioheat model for able-bodied person is selected to be modified. Changes in cardiovascular responses and energy expenditure in TP are implemented. The model is validated with steady-state and transient experiments in literature.